Correlated Study of Material Interaction Between Capillary Printed Eutectic Gallium Alloys and Gold Electrodes. Issue 42 (8th September 2022) - Hussain, Navid; Scherer, Torsten; Das, Chittaranjan; Heuer, Janis; Debastiani, Rafaela; Gumbsch, Peter; Aghassi‐Hagmann, Jasmin; Hirtz, Michael
Abstract: Liquid metals (LMs) play a growing role in flexible electronics and connected applications. Here, LMs come into direct contact with metal electrodes thus allowing for corrosion and additional alloying, potentially compromising device stability. Nevertheless, comprehensive studies on the interfacial interaction of the materials are still sparse. Therefore, a correlated material interaction study of capillary‐printed Galinstan (eutetic alloy of Ga/In/Sn) with gold surfaces and electrodes is conducted. Comprehensive application of optical microscopy, vertical scanning interferometry, scanning electron microscopy/spectroscopy, x‐ray photon spectroscopy, and atomic force microscopy allow for an in depth characterization of the spreading process of LM lines on gold films, revealing the differential spread of the different LM components and the formation of intermetallic nanostructures on the surface of the surrounding gold film. A model for the growth process based on the penetration of LM along the gold film grain boundaries is proposed based on the obtained time‐dependent characterization. The distribution of gold, Galinstan, and intermetallic phases in a gold wire dipped into LM is observed using X‐ray nano tomography as a complementary view on the internal nanostructure. Finally, resistance measurements on LM lines connecting gold electrodes over time allow to estimate the influence on the material interaction on electronic applications. Abstract : Flexible electronics make frequent use of liquid metals as, e.g., eutetic gallium alloys, often in direct contact with classical electrode materials such as gold. Therefore, the interfacial interaction of such materials is of high interest for these applications. A correlated study with complementary chemical and morphological characterization techniques offers insights into the evolution of such contacts over time.